What Does Channel Say? Understanding How Social Media Social Capital Facilitates COVID‐19‐Related Information‐Seeking and Opinion‐Expression on Two Types of Platforms: User‐oriented versus Content‐oriented. Issue 1 (13th October 2021) - Hu, Junwen
Abstract: Social capital (i.e., resources obtained from social relationships) facilitates informational use of media, yet how in detail the mechanism functions in a multi‐platform social media environment remains underexplored. Taking an affordance approach, this study aimed to investigate the differentiated effects of social media social capital on COVID‐19‐related information behaviors on user‐oriented and content‐oriented social media (USM&CSM). It was hypothesized that information exposure on USM mediates the relationship between social capital and information‐seeking intention, whereas exposure on CSM was expected to mediate the relationship between social capital and opinion expression. Web‐based survey data collected among Chinese social media users (N = 256) supported the hypotheses, and in‐depth interviews (N = 15) further revealed how people explored the affordances of different platforms to enjoy the information resources. Implications were discussed.